Expression of Prostate-Specific Membrane Antigen (PSMA) on Biopsies Is an Independent Risk Stratifier of Prostate Cancer Patients at Time of Initial Diagnosis - Hupe, Marie Christine; Philippi, Christian; Roth, Doris; Kümpers, Christiane; Ribbat-Idel, Julika; Becker, Finn; Joerg, Vincent; Duensing, Stefan; Lubczyk, Verena Helena; Kirfel, Jutta; Sailer, Verena; Kuefer, Rainer; et al. (Frontiers in Oncology, 2018)
Background: Stratifying PCa patients into risk groups at time of initial diagnosis enabling a risk-adapted disease management is still a major clinical challenge. Existing studies evaluating the prognostic potential of PSMA for PCa were performed on radical prostatectomy specimens (RPE), i.e. decision making for disease management was already completed at time of sample analysis. Aim of our study was to assess the prognostic value of PSMA (prostate-specific membrane antigen) expression for prostate cancer (PCa) patients on biopsies at time of initial diagnosis. Methods: PSMA expression was assessed by immunohistochemistry on 294 prostate biopsies with corresponding RPE, 621 primary tumor foci from 242 RPE, 43 locally advanced or recurrent tumors, 34 lymph node metastases, 78 distant metastases and 52 benign prostatic samples. PSMA expression was correlated with clinico-pathologic features. Primary endpoint was recurrence free survival. Other clinicopathologic features included WHO/ISUP grade groups, PSA serum level, TNM-stage, and R-status. Chi-square test, ANOVA-analyses, Cox-regression and log-rank tests were performed for statistical analyses. Results: High PSMA expression on both biopsy and RPE significantly associates with a higher risk of disease recurrence following curative surgery. The 5-year-recurrence free survival rates were 88.2%, 74.2%, 67.7% and 26.8% for patients exhibiting no, low, medium or high PSMA expression on biopsy, respectively. High PSMA expression on biopsy was significant in multivariate analysis predicting a 4-fold increased risk of disease recurrence independently from established prognostic markers. PSMA significantly increases during PCa progression. Conclusion: PSMA is an independent prognostic marker on biopsies at time of initial diagnosis and can predict disease recurrence following curative therapy for PCa. Our study proposes the application of the routinely used IHC marker PSMA for outcome prediction and decision making in risk-adapted PCa management on biopsies at time of initial diagnosis.